2016
DOI: 10.1051/epjn/e2015-50032-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of thorium-uranium in pebble-bed fluoride salt-cooled high temperature reactor

Abstract: Abstract. Sustainability of thorium fuel in a Pebble-Bed Fluoride salt-cooled High temperature Reactor (PB-FHR) is investigated to find the feasible region of high discharge burnup and negative Flibe (2LiF-BeF 2 ) salt Temperature Reactivity Coefficient (TRC). Dispersion fuel or pellet fuel with SiC cladding and SiC matrix is used to replace the tristructural-isotropic (TRISO) coated particle system for increasing fuel loading and decreasing excessive moderation. To analyze the neutronic characteristics, an eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…MOBAT code system was developed for burnup analysis for arbitrary core models. Its correctness and effectiveness have been intensively proved 17 . The flow chart of the equilibrium LSFR reference core as shown in Figure 4 was the same with the previous study for detailed description in the previous papers 14,16 .…”
Section: Model and Methodologymentioning
confidence: 80%
See 1 more Smart Citation
“…MOBAT code system was developed for burnup analysis for arbitrary core models. Its correctness and effectiveness have been intensively proved 17 . The flow chart of the equilibrium LSFR reference core as shown in Figure 4 was the same with the previous study for detailed description in the previous papers 14,16 .…”
Section: Model and Methodologymentioning
confidence: 80%
“…The TRISO‐based pebble bed fluoride‐salt‐cooled high‐temperature reactor (PB‐FHR) is not suitable for thorium/uranium breeding due to low fuel loading (not beyond 5 vol%) and strong neutron moderating ability. Guifeng Zhu et al 9‐10 put forward a new thorium/uranium breeding PB‐FHR using dispersion fuel particles. Their study suggested that the maximum discharge burnup for dispersion‐based PB‐FHR was more than 200 MWd/kgHM whereas keeping thorium‐uranium sustainable and coolant temperature reactivity coefficient negative.…”
Section: Introductionmentioning
confidence: 99%